Development of a sustainable multilayer chitosan-based nanocomposite membrane for effective removal of DB78 dye from aqueous solution - Ahmed Eteba; Mohamed Bassyouni; Medhat H. Elzahar; Mohamed Z. El-shekhiby (Results in Engineering)
Membrane technologies have emerged as a promising alternative to traditional, energy-intensive separation methods across various industrial sectors including textile wastewater treatment. Traditional polymeric membranes however often face challenges such as low filtration performance and weak mechanical properties. Recent studies have focused on the fabrication of biocompatible nanocomposite membranes with improved performance characteristics. This study presented the development and characterization of a multi-layer chitosan-based nanocomposite membrane (MLN) incorporating amino-functionalized multi-walled carbon nanotubes (MWCNTs-NH₂) and cellulose nanocrystals (CNCs) into the chitosan matrix. The optimized membrane with 0.2 wt.% MLN-0.2 loading of both nanofillers demonstrated enhanced dye removal efficiency, water permeability, and mechanical stability. Characterization via SEM, EDS, AFM, porosity, wettability, mechanical properties, and FTIR confirmed these improvements. Under optimized conditions, the MLN-0.2 achieved a water flux of 3.2 L m⁻² h⁻¹ bar⁻¹ at 6.8 bar and a dye rejection rate of 100 % at pH 7. The flux recovery ratio of 87 % after three filtration cycles demonstrated its antifouling capability. Structural modifications by the nanofillers increased membrane porosity from 30.6 % to 41 % and reduced the mean pore size from 6.8 nm to 5.9 nm, contributing to high permeability and selectivity. Additionally, the membrane's mechanical strength improved by 42 %, and hydrophilicity increased, reducing the water contact angle from 60.2° to 39°. These results highlighted the MLN-0.2 membrane as a durable and high-performance solution for textile wastewater treatment addressing key performance and durability challenges while utilizing the biodegradable properties of its components.